2020
DOI: 10.3389/fpsyg.2020.01397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regulatory Focus and Emotions on Information Preferences: The Affect-as-Information Perspective

Abstract: This study explored the effects of regulatory focus and emotions on information preferences, specifically information selection preferences (experiment 1) and implicit information preferences (experiment 2). Our findings revealed that, in the promotionfocused condition, individuals preferred hedonic information (vs. functional information) when they were happy (vs. sad). However, emotions' effects on information preferences were attenuated in the prevention-focused condition. In experiment 3, we tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Moreover, the meta-analysis conducted by Fodor and Pintea (2017) indicates that unlike positive emotions, negative emotions do not have a significant impact on business performance. Hence, we argue that a top manager’s reliance on negative emotions when forming responses can be dependent on their intrinsic motivation (Marroquín et al, 2016), where regulatory focus has shown to significantly influence how individuals respond to emotional information (Brockner and Higgins, 2001; Wang et al, 2020).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Moreover, the meta-analysis conducted by Fodor and Pintea (2017) indicates that unlike positive emotions, negative emotions do not have a significant impact on business performance. Hence, we argue that a top manager’s reliance on negative emotions when forming responses can be dependent on their intrinsic motivation (Marroquín et al, 2016), where regulatory focus has shown to significantly influence how individuals respond to emotional information (Brockner and Higgins, 2001; Wang et al, 2020).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Furthermore, the current research extends the literature on regulatory focus and emotion. Prior studies have found that individuals in a promotion-focused condition are more affected by emotion than are those in a prevention-focused condition [ 35 ]. A happy mood has a greater influence on individuals with a promoting orientation than on those who are in a sad mood [ 36 ]; however, in the current research, we used information related to water saving as the experimental materials, and we found that the sadness emotion had a greater impact on individuals with a prevention focus than on those with a promotion focus.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the first task was a recall task. Participants in the promotion-focused group were asked to write down their ideals and aspirations, and those in the prevention-focused group were requested to write down their oughts and obligations (Freitas and Higgins, 2002;Wang et al, 2020). After this, all participants were asked to complete a paper-pencil maze task to further understand their promotion or prevention focuses (Friedman and Förster, 2001).…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Please choose between options A and B based on your current thoughts: (A) economic information; (B) entertainment information." Participants chose one of these two options to represent their information choice preferences (Wang et al, 2020). After that, participants completed a questionnaire that assessed explicit information preference.…”
Section: Procedures and Materialsmentioning
confidence: 99%
See 1 more Smart Citation